Physicians' age and sex influence breaking bad news to elderly cancer patients. Beliefs and practices of 50 Italian oncologists: the G.I.O.Ger study. Issue 5 (7th June 2012) - Locatelli, C.; Piselli, P.; Cicerchia, M.; Repetto, L.
Abstract Purpose We attempt to shed light on the truth‐telling attitudes and practices of oncologists working with a geriatric population in Italy. Participants and method Physicians caring for cancer patients were asked to complete a specific survey centred on their beliefs, attitudes and practices towards truth telling to elderly cancer patients. Results Of 50 physicians surveyed, 68% were men. Physicians practising in the south of Italy were significantly older and more likely to be of male gender in comparison with physicians practising from the north and central areas. Eighty‐four per cent of physicians consider the family to be an obstacle to a direct communication with the elderly. Forty‐four per cent of male physicians who are faced with a family's request of nondisclosure talk with the patient, whereas 37.5% of female physicians talk with the family. For 60% of interviewed physicians, the reason underpinning the caregiver's choice of nondisclosure is to delay the emotional confrontation. Conclusions We observed that variability of disclosure is related not only to the patient's age but also to the physicians' age and sex and to the geographic area where physicians work. The results also show that both caregivers and physicians are concerned by the emotional aspects related to clinical information. Italian oncologists have to learn and implement 'comprehensive' communication skills and have to promote an integration of the information needs of patient and caregivers, according to their socio‐cultural affiliation, within the communication techniques. Copyright © 2012 John Wiley & Sons, Ltd.